Epigenetic mechanism of L-type calcium channel β-subunit downregulation in short QT human induced pluripotent stem cell-derived cardiomyocytes with CACNB2 mutation: basic science - Zhong, Rujia; Zhang, Feng; Yang, Zhen; Li, Yingrui; Xu, Qiang; Lan, Huan; Cyganek, Lukas; El-Battrawy, Ibrahim; Zhou, Xiao-Bo; Akın, Ibrahim; Borggrefe, Martin (Europace, 2022)
A loss-of-function mutation in L-type calcium (Ca2+) channel subunit gene CACNB2 has been reported to cause short QT syndrome subtype 5 (SQT5). However, the mechanism underlying the loss-of-function of the Ca2+ channel has not been clarified. In the present study, we aim to explore the DNA methylation mechanism of L-type Ca2+ channel downregulation in human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) of SQT5.The hiPSC-CMs were generated from a healthy donor and a SQT5 patient carrying the CACNB2 variant c.1439C > T/p.S480L. The variant was genetically corrected using ribonucleoprotein-based CRISPR/Cas9 technique to obtain an isogenic control cell line. The action potential (AP) and Ca2+ current were measured by patch clamp. Protein expression levels were determined by western blotting. Dot blotting and bisulfite sequence were performed for epigenetic study. Our results showed that AP durations at 10% repolarization (APD10) and 50% repolarization (APD50) were significantly shortened in SQT5 cells and both the expression level of the β-subunit and channel current of L-type Ca2+ channel were reduced. Besides, an increased level of whole-genome DNA methylation and DNA methylation of CpG island in the promoter region of CACNB2 gene was detected. Overexpression of demethylation enzyme could rescue the decreased expression of CACNB2 and the L-type Ca2+ current.In SQT5 hiPSC-CMs carrying the CACNB2-S480L variant, the decreased L-type Ca2+ current resulting from decreased CACNB2 protein expression was caused by enhanced methylation in the promoter region of the CACNB2 gene and upregulation of DNA methyltransferases might be one of the mechanisms.